Influence of body composition assessment with bioelectrical impedance vector analysis in cancer patients undergoing surgery - Cai, Bin; Luo, Lan; Zhu, Chenping; Meng, Liping; Shen, Qing; Fu, Yafei; Wang, Mingjie; Chen, Sue (Frontiers in Oncology, 2023)
Background Malnutrition is common in patients undergoing surgery for cancers and is a risk factor for postoperative outcomes. Body composition provides information for precise nutrition intervention in perioperative period for improving patients’ postoperative outcomes. Objection The aim was to determine changes in parameters of body composition and nutritional status of cancer patients during perioperative period. Methods A total of 92 patients diagnosed with cancer were divided into gastrointestinal and non-gastrointestinal cancer group according to different cancer types. The patients body composition assessed by bioelectrical impedance vector analysis (BIVA) on the day before surgery, postoperative day 1 and 1 day before discharge. The changes between two groups were compared and the correlation between body composition and preoperative serum nutritional indexes was analyzed. Results The nutritional status of all patients become worse after surgery, and phase angle (PA) continued to decrease in the perioperative period. Fat-free mass (FFM), fat-free mass index (FFMI), skeletal muscle mass (SMM), extracellular water (ECW), total body water (TBW), hydration, and body cell mass (BCM) rise slightly and then fall in the postoperative period in patients with gastrointestinal cancer, and had a sustained increase in non-gastrointestinal patients, respectively (P<0.05). Postoperative body composition changes in patients with gastrointestinal cancer are related to preoperative albumin, pre-albumin, hemoglobin, and C-reactive protein (P<0.05), whereas postoperative body composition changes in patients with non-gastrointestinal cancer are related to age (P<0.05). Conclusions Significant changes in body composition both in patients with gastrointestinal cancer and non-gastrointestinal cancer during perioperative period are observed. Changes in body composition for the cancer patients who undergoing surgery are related to age and preoperative serum nutrition index.